184k views
0 votes
Solve the inequality for –5.3 ≥ 6.7 + 4.3 + q

User Sahil Dhir
by
5.0k points

2 Answers

3 votes

Answer: q ≤ -163/10

Explanation:

Reformatting the input :

Changes made to your input should not affect the solution:

(1): "4.3" was replaced by "(43/10)". 3 more similar replacement(s)

Rearrange:

Rearrange the equation by subtracting what is to the right of the greater equal sign from both sides of the inequality :

-(53/10)-((67/10)+(43/10)+q)≥0

Step by step solution :

Step 1 :

43

Simplify ——

10

Equation at the end of step 1 :

53 67 43

(0-——)-((——+——)+q) ≥ 0

10 10 10

Step 2 :

67

Simplify ——

10

Equation at the end of step 2 :

53 67 43

(0 - ——) - ((—— + ——) + q) ≥ 0

10 10 10

Step 3 :

Adding fractions which have a common denominator :

3.1 Adding fractions which have a common denominator

Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

67 + 43 11

——————— = ——

10 1

Equation at the end of step 3 :

53 11

(0 - ——) - (—— + q) ≥ 0

10 1

Step 4 :

53

Simplify ——

10

Equation at the end of step 4 :

53

(0 - ——) - (q + 11) ≥ 0

10

Step 5 :

Rewriting the whole as an Equivalent Fraction :

5.1 Subtracting a whole from a fraction

Rewrite the whole as a fraction using 10 as the denominator :

q + 11 (q + 11) • 10

q + 11 = —————— = —————————————

1 10

Equivalent fraction : The fraction thus generated looks different but has the same value as the whole

Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator

Adding fractions that have a common denominator :

5.2 Adding up the two equivalent fractions

Add the two equivalent fractions which now have a common denominator

Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

-53 - ((q+11) • 10) -10q - 163

——————————————————— = ——————————

10 10

Step 6 :

Pulling out like terms :

6.1 Pull out like factors :

-10q - 163 = -1 • (10q + 163)

Equation at the end of step 6 :

-10q - 163

—————————— ≥ 0

10

Step 7 :

7.1 Multiply both sides by 10

7.2 Multiply both sides by (-1)

Flip the inequality sign since you are multiplying by a negative number

10q+163 ≤ 0

7.3 Divide both sides by 10

q+(163/10) ≤ 0

User Max Tet
by
5.9k points
1 vote

Answer:

-16.3 ≥ q

Explanation:

–5.3 ≥ 6.7 + 4.3 + q

Combine like terms

–5.3 ≥ 11 + q

Subtract 11 from each side

–5.3-11 ≥ 11-11 + q

-16.3 ≥ q

User Kenarsuleyman
by
5.4k points